2019
DOI: 10.1108/mi-05-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Design of microfluidic experimental setup for the detection of heavy metal ions using piezoresistive BioMEMS sensor

Abstract: Purpose This paper aims to propose a new microfluidic portable experimental platform for quick detection of heavy metal ions (HMIs) in picomolar range. The experimental setup uses a microfabricated piezoresistive sensor (MPS) array of eight cantilevers with ion-selective self-assembled monolayer's (SAM). Design/methodology/approach Most of the components used in this experimental setup are battery operated and, hence, portable to perform the on-field experiments. HMIs (antigen) and thiol-based SAM (antibody)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…To test our functionalised QCM sensor on a VNA‐based portable experimental platform for microfluidic application to selective detect Hg 2+ ions, we have performed the experiments for checking the sensitivity towards the Hg 2+ ions. We have already investigated selectivity of HCys‐PDCA for selectively detected the Hg 2+ ions using the MEMS‐based piezoresistive experimental platform by Rotake et al [54]. Here, we have focused on the detection of Hg 2+ ions using portable and quick VNA‐based frequency sensing approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test our functionalised QCM sensor on a VNA‐based portable experimental platform for microfluidic application to selective detect Hg 2+ ions, we have performed the experiments for checking the sensitivity towards the Hg 2+ ions. We have already investigated selectivity of HCys‐PDCA for selectively detected the Hg 2+ ions using the MEMS‐based piezoresistive experimental platform by Rotake et al [54]. Here, we have focused on the detection of Hg 2+ ions using portable and quick VNA‐based frequency sensing approach.…”
Section: Resultsmentioning
confidence: 99%
“…So there is a need for the design and development of the portable experimental platform for on‐site mercurydetection. We have already investigated SAM of homocysteine (HCys)‐pyridinedicarboxylic acid (PDCA) for selectively detected the Hg 2+ ions using MEMS‐based piezoresistive experimental platform by Rotake et al [54, 55]. This microcantilever‐based approach is capable of detecting mercury ions at the picomolar range but not suitable for a higher concentration limit provided by WHO.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously investigated SAMs of homocysteine (HCys) and pyridinedicarboxylic acid (PDCA) for the selective sensing of Hg(II) ions using a portable piezoresistive platform [39,40]. Experimental results confirmed that proposed setup is capable of sensing in the picomolar range.…”
Section: Introductionmentioning
confidence: 87%
“…We have previously investigated SAM of Homocysteine (HCys)-pyridinedicarboxylic acid (PDCA) for selective sensing of the Hg 2 ions using a portable piezoresistive platform [39,40] and exper-imental results confirmed that proposed setup is capable of picomolar sensing. In this paper, we have used the previously designed portable piezoresistive platform to selectively capture the Cadmium ions in the picomolar range.…”
Section: Introductionmentioning
confidence: 93%